Randomized placebo-controlled EPPIC trials of AST-120 in CKD - Schulman, Gerald; Berl, Tomas; Beck, Gerald J.; Remuzzi, Giuseppe; Ritz, Eberhard; Arita, Kiyoshi; Kato, Akira; Shimizu, Miho (Journal of the American Society of Nephrology, 2015)
Reduced GFR in patients with CKD causes systemic accumulation of uremic toxins, which has been correlated with disease progression and increased morbidity. The orally administered spherical carbon adsorbent AST-120 reduces systemic toxin absorption through gastrointestinal sequestration, which may slow disease progression in these patients. The multinational, randomized, double-blind, placebo-controlled Evaluating Prevention of Progression in CKD (EPPIC)-1 and EPPIC-2 trials evaluated the effects of AST-120 on the progression of CKD when added to standard therapy. We randomly assigned 2035 adults with moderate to severe disease (serum creatinine at screening, 2.0-5.0 mg/dl for men and 1.5-5.0 mg/dl for women) to receive either placebo or AST-120 (9 g/d). The primary end point was a composite of dialysis initiation, kidney transplantation, and serum creatinine doubling. Each trial continued until accrual of 291 primary end points. The time to primary end point was similar between the AST-120 and the placebo groups in both trials (EPPIC-1: hazard ratio, 1.03; 95% confidence interval, 0.84 to 1.27; P=0.78) (EPPIC-2: hazard ratio, 0.91; 95% confidence interval, 0.74 to 1.12; P=0.37); a pooled analysis of both trials showed similar results. The estimated median time to primary end points for the placebo groups was 124 weeks for power calculations, but actual times were 189.0 and 170.3 weeks for EPPIC-1 and EPPIC-2, respectively. Thus, disease progression was more gradual than expected in the trial populations. In conclusion, the benefit of adding AST-120 to standard therapy in patients with moderate to severe CKD is not supported by these data.